Linking Aboveground Traits to Root Traits and Local Environment: Implications of the Plant Economics Spectrum - Shen, Yong; Gilbert, Gregory S.; Li, Wenbin; Fang, Miao; Lu, Huanping; Yu, Shixiao (Frontiers in Plant Science, 2019)
The plant economics spectrum proposes that ecological traits are functionally coordinated and adapt along environmental gradients. However, empirical evidence is mixed about whether aboveground and root traits are consistently linked and which environmental factors drive functional responses. Here we measure the strength of relationships between above and root traits, and examine whether traits are adapted along gradients of light and soil fertility, based on the censuses of 17,148 seedlings of 57 species across 10-year in a subtropical forest. We found that aboveground traits were good predictors of root traits; specific leaf area, dry matter, nitrogen and phosphorus content were strongly correlated with root tissue density and specific root length. Traits showed patterns of adaptation along the gradients of soil fertility and light, species with fast resource-acquisitive strategies were more strongly associated with high soil phosphorus, potassium, openness, and with low nitrogen, organic matter conditions. This demonstrate the potential to estimate belowground traits from known aboveground traits in seedling communities, and suggest that soil fertility is the main factor driving functional responses. Our results extend our understanding of how ecological strategies shape potential responses of plant communities to environmental change.